JAPANESE CORPORATE GOVERNANCE REFORM : WHAT IS REQUIRED FOR EFFECTIVE FUNCTIONING OF OUTSIDE DIRECTORS ? - Suzuki, Masaru (Faculty of Law, Universitas Sebelas Maret, 2019)
The topic of outside directors’ functions has been attracting significant attention for many years now, especially in the discussions about corporate governance reform in Japan. Over the last two decades, most listed Japanese companies have voluntarily introduced outside directors into their boardrooms, in line with the gradual change in an overall corporate governance system toward a monitoring board model moving away from the more traditional management board model. It appears the recent trend is for companies to add outside directors to their boards of directors to increase corporate values. In the midst of transforming the management board model into the monitoring board model, closely reexamining the functions of outside directors is necessary. What can be concluded from the lessons learned from recent corporate scandals and the discussions concerning the functions of outside directors is: (1) outside directors should be truly independent from the company’s management; and (2) outside directors need access to the company’s corporate information in order to prevent corporate scandals and to provide appropriate advice to the company’s management. This paper aims at considering how to make outside directors more effective and their roles more substantial, based on the history of corporate governance reform in Japan.